Influence of the incorporation of triclosan methacrylate on the physical properties and antibacterial activity of resin composite - Andreia Bolzan de Paula; Roberta Caroline Bruschi Alonso; Jesus Roberto Taparelli; Jéssica Rodrigues Camassari; Lúcia Helena Innocentini-Mei; Lourenço Correr-Sobrinho; Regina M. Puppin-Rontani
Abstract The incorporation of antimicrobials in the composites as an attempt to reduce bacterial adhesion without jeopardizing mechanical properties is a challenge for Dentistry. Objective: To evaluate the bacterial adhesion and physical properties of a composite containing the methacrylate triclosan- derivative monomer (TM). Methodology: TM was synthesized and added to an experimental composite. Samples were divided into two groups: Control and TM (13.4 wt%). Antibacterial Activity: Three specimens of each material were prepared and placed on bacterial suspensions of Streptococcus mutans for 1, 5 and 10 days. After these periods the counting of the colonies (log10) was performed. Assays was performed in triplicate. Physical Properties: Three-body Abrasion (TBA): Ten specimens of each material were prepared and stored at 37°C/24 h. The surface roughness (Ra) and hardness (KHN) were analyzed. Next, the specimens were submitted to abrasive wear (30,000 cycles) and re-evaluated for Ra and KHN; Sorption/solubility (SS): cylindrical specimens (n=10) were prepared and weighted. The specimens were immersed in deionized water for 7 days at 37°C and then their weight was verified again. SS were calculated using accepted formulas; Diametral tensile strength (DTS): specimens (n=10) underwent test performed in an Instron universal testing machine at a crosshead speed of 1 mm/min. Data were submitted to appropriate statistical tests according to data distribution and assay (p<0.05). Results: Bacterial Adhesion: TM showed a significant reduction on biofilm accumulation in the evaluated periods: 1 day (1.537±0.146); 5 days (2.183±0.138) and 10 days (4.469±0.155) when compared with Control: 1 day (4.954±0.249); 5 days (5.498±0.257) and 10 days (6.306±0.287). Physical Properties: For TBA, SS and DTS no significant difference was found between groups Control and TM. The incorporation of methacrylate triclosan-based monomer in the experimental composite reduce bacterial adhesion of S. mutans and did not affect important polymer properties.